Ready to tie the knot? : understanding millennials’ perceptions on dating, marriage and family - Lieu, Hui Ying (2018)
The phenomena of rising singlehood, late marriages and childbearing in Singapore contributed to its sub-replacement fertility and ageing population, leading to social, political and economic implications. Therefore, the state made continual efforts to increase its population by targeting young adults through matchmaking events and population policies. This explorative study analyses twenty-nine in-depth semi-structured interviews with never- married Singaporean millennials to understand their perceptions of dating, marriage and family formation, while addressing the literature gap in the millennials’ dating culture. We found that while marriage and family were highly desired by millennials, their lack of economic resources and conservative mind-set pose as barriers to early marriage. With a persisting trend towards delayed marriages, we suggest that it stems from their delayed transition into adulthood, constant negotiations between traditional beliefs and modern norms, and their pragmatic mind-set in marriage and family formation.